A novel approach for developing left bundle branch pacing and left bundle branch block in a canine model. (26th February 2023) - Hu, Yiran; Cheng, Sijing; He, Pengkang; Huang, Hao; Li, Hui; Weng, Sixian; Sun, Xue Rong; Gu, Min; Niu, Hongxia; Liu, Xi; Jin, Han; Zhou, Xiaohong; et al.
Abstract: Background and Objective: Left bundle branch pacing (LBBP) has shown the benefits in the treatment of dyssynchronous heart failure (HF). The purpose of this study was to develop a novel approach for LBBP and left bundle branch block (LBBB) in a canine model. Methods: A "triangle‐center" method by tricuspid valve annulus angiography for LBBP implantation was performed in 6 canines. A catheter was then applied for retrograde His potential recording and left bundle branch (LBB) ablation simultaneously. The conduction system was stained to verify the "triangle‐center" method for LBBP and assess the locations of the LBB ablation site in relation to the left septal fascicle (LSF). Results: The mean LBB potential to ventricular interval and stimulus‐peak left ventricular activation time were 11.8 ± 1.2 and 35.7 ± 3.1 ms, respectively. The average intrinsic QRS duration was 44.7 ± 4.7 ms. LBB ablation significantly prolonged the QRS duration (106.3 ± 8.3 ms, p  < .001) while LBBP significantly shortened the LBBB‐QRS duration to 62.5 ± 5.3 ms ( p  < .001). After 6 weeks of follow‐up, both paced QRS duration (63.0 ± 5.4 ms; p  = .203) and LBBB‐QRS duration (107.3 ± 7.4 ms; p  = .144) were unchanged when comparing to the acute phase, respectively. Anatomical analysis of 6 canine hearts showed that the LBBP lead‐tip was all placed in LSF area. Conclusion: The new approach for LBBP and LBBB canine model was stable and feasible to simulate the clinical dyssynchrony and resynchronization. It provided a useful tool to investigate the basic mechanisms of underlying physiological pacing benefits. Abstract : Study flow of the animal model development and application. LBBP: left bundle branch pacing; LBBB: left bundle branch block; TVA: tricuspid valve annulus; HF: heart failure. LBB: left bundle branch.